EFFECT OF PRETREATMENT ON ORGANOLEPTIC EVALUATION OF SUBLIMATION-DRIED APRICOT PRODUCTS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The article presents data from studies on the organoleptic evaluation of freeze-dried apricot products. In particular, freeze-drying technology and primary processing processes have a significant impact on the organoleptic properties of apricot products.
Keywords: Apricot, apricot varieties, dry product, drying, organoleptic evaluation.